2014
DOI: 10.1557/jmr.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

A diffusion-viscous analysis and experimental verification of defect formation in sintered silver bond-line

Abstract: The low-temperature joining technique (LTJT) by silver sintering is being implemented by major manufacturers of power electronic devices and modules for bonding power semiconductor chips. A common die-attach material used with LTJT is a silver paste consisting of silver powder (micrometer-or nanometer-sized particles) mixed in organic solvent and binder formulation. It is believed that the drying of the paste during the bonding process plays a critical role in determining the quality of the sintered bond-line.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…1 a and parameters to demonstrate the aste during drying. The detailed ur previous work [11]. During the drying process, the paste is constrained on the x-y plane by the chip and substrate, and both the chip and substrate are considered as rigid bodies undergoing no deformation.…”
Section: Solvent Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…1 a and parameters to demonstrate the aste during drying. The detailed ur previous work [11]. During the drying process, the paste is constrained on the x-y plane by the chip and substrate, and both the chip and substrate are considered as rigid bodies undergoing no deformation.…”
Section: Solvent Removalmentioning
confidence: 99%
“…In our recent studies, we developed a mathematical model based on diffusion of solvent molecules and viscousflow mechanics of a silver paste to show that drying of the paste in the bonding process is a critical step in determining the bond-line microstructural and mechanical quality [11]. Our modeling results showed that stresses and strains generated in the shrinking silver paste were responsible for observed delamination and cracking in the sintered bond-line [12].…”
Section: Introductionmentioning
confidence: 99%
“…Loading [MathJax]/jax/output/CommonHTML/jax.js An alternative bonding approach, that has been investigated to address the abovementioned limitations, is nanoparticle sintering. Various sintering nanoparticles have been explored by virtue of their high melting temperatures and superior electrical and thermal conductivities [15][16][17][18][19]. Unlike Ag-nanoparticle sintering, that is not suitable for practical application because of the high cost and low ion-migration resistance of Ag nanoparticles [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, Cu nanoparticle sintering is unsuitable for electronic devices because of the weak oxidation resistance of Cu [22]. Besides, the nanoparticle paste contains, various organic substances, including solvents, capping molecules and binders, which are added to tailor the properties of the paste [19]. For example, polyvinylpyrrolidone serves as a capping molecule to control the size of the nanoparticles and protect them against oxidation [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative bonding approach, that has been investigated to address the abovementioned limitations, is nanoparticle sintering. Various sintering nanoparticles have been explored by virtue of their high melting temperatures and superior electrical and thermal conductivities [15][16][17][18][19]. Unlike Ag-nanoparticle sintering, that is not suitable for practical application because of the high cost and low ion-migration resistance of Ag nanoparticles [20].…”
Section: Introductionmentioning
confidence: 99%